(untitled) (Research, Society and Development, 2022)
Introduction: The intestinal microbiota has a strong relationship with psychological disorders and physical disproportion. Such factors can be observed in the alteration of sleep, excessive sadness and in addition, even in cases of profound profound. In this sense, it is important to analyze the relationship between the Microbiota and the quality of life. Objective: To analyze how intestinal dysbiosis is associated with depression. Methodology: This is a literature review with a deductive approach. Results: From the possible literature study, it was possible to observe the importance of the analysis of the intestinal microbiota in the individual with problems or mental disorders: depression. Discussion of the results: The importance of intestinal modification was presented with the use of immunomodulatory axes-modulators for intestinal alterations: basic mechanisms, such as depression and its reactions. Conclusion: The development of the present study of advanced study of the intestinal microbiota aims to elucidate the microbiota, starting from the point of the intestine-brain, identifying the main members that contribute to the divergent organs, such as the intestine and the brain.